Considerations of tooth extraction during pregnancy - M. Hendra Chandha (Journal of Dentomaxillofacial Science, 2007)
regnancy is a common sense. However, when dental care, is likely to perform inparticular tooth extraction, a dentist should be aware of any systemic changes occurredduring pregnancy that can lead to several problems in dental practice. This paper is aimedto discuss the consideration of taking dental radiography and prescribing medicine for anexpectant mother that can't be avoided during oral surgery.